Transforming polypropylene waste into transparent anti-corrosion weather-resistant and anti-bacterial superhydrophobic films - Saleem, Junaid (2024)
The global pollution crisis arising from the accumulation of plastic in landfills and the environment necessitates addressing plastic waste issues. Notably, polypropylene (PP) waste accounts for 20% of total plastic waste and holds promise for hydrophobic applications in the realm of recycling. Herein, the transparent and non-transparent superhydrophobic films made from waste PP are reported. A hierarchical structure with protrusions is induced through spin-casting and thermally induced phase separation. The films had a water contact angle of 159° and could vary in thickness, strength, roughness, and hydrophobicity depending on end-user requirements. The Bode plot indicated enhanced corrosion resistance in the superhydrophobic films. Antibacterial trials with Escherichia coli and Staphylococcus aureus microbial solutions showed that the superhydrophobic film had a significantly lower rate of colony-forming units compared to both the transparent surface and the control blank sample. Moreover, a life cycle assessment revealed that the film production resulted in a 62% lower embodied energy and 34% lower carbon footprint compared to virgin PP pellets sourced from petroleum. These films exhibit distinctiveness with their dual functionality as coatings and freestanding films. Unlike conventional coatings that require chemical application onto the substrate, these films can be mechanically applied using adhesive tapes on a variety of surfaces. Overall, the effective recycling of waste PP into versatile superhydrophobic films not only reduces environmental impact but also paves the way for a more sustainable and eco-friendly future.